Comparative study on classifications of AJCC 8th and 7th in the patients with tongue squamous cell carcinoma. (10th March 2022) - Yu, Shun; Yu, Zi‐Li; Ye, Zi‐Wu; Jia, Jun
Abstract: Objectives: Depth of invasion (DOI) is the most important predictor for lymph node metastasis in early‐stage oral cancer. This study aims to investigate the effects of the different classifications of AJCC 7th and 8th on predicting lymph node metastasis and the optimal cutoff point for DOI predicting the lymph node metastasis in patients with tongue squamous cell carcinoma (TSCC). Materials and methods: We performed a retrospective study in 208 TSCC patients in early T stage without clinical or radiological signs of lymph node metastasis. Those patients were treated with elective neck dissection (END) between April 2019 and December 2020. And the relation between DOI and lymph node metastasis was analyzed. Results: Metastases were found in 58 of 208 patients (27.88%). Of those 58 patients, the mean DOI was 8.311 mm compared to 5.425 mm in patients without metastases ( p  < 0.0001). The receiver operating characteristic curve (ROC curve) showed an area under the curve of 0.7066 with the most optimal cutoff point on a DOI of 4.050 mm (sensitivity 86.21%, specificity 52%). Linear regression analysis (1 mm ≤ DOI ≤6 mm) revealed that a DOI ≥ 3.211 mm predicated an incidence of occult lymph node metastasis greater than 20%. Regional metastases were found in 12.82% of patients with DOI ≤ 4.0 mm. Within the entire cohort, 60 cases (28.85%) got upgraded with respect to T stage. No tumor underwent downstaging. Conclusion: The 8th edition provides better lymph node metastasis prediction for TSCC than the 7th. And DOI is a poor predictor for regional metastasis in patients with early T stage clinically node‐negative TSCC. END in patients with early‐stage TSCC should be performed in patients with DOI ≥ 3.211 mm.